Enhancing Students’ Scientific Literacy through Deep Learning: A Systematic Review of Science Learning Models - Hendra Ramadhan; Sulistyo Saputro; Lina Mahardiani; Mlathi Anggayuh Jati; Tia Istiana Potabuga (Universitas Syiah Kuala, 2026)
Scientific literacy is a key competency emphasized in the PISA 2025 framework and serves as a benchmark for science education quality in Indonesia. However, Indonesian students’ performance remains below the OECD average, indicating the need for more effective and conceptually grounded learning approaches. This study aims to systematically review science learning models that enhance students’ scientific literacy from a deep learning perspective. The review followed the PRISMA 2020 protocol and analyzed forty-two articles published between 2015 and 2025 from scopus, web of science, springerlink, eric, and google scholar. Thematic analysis identified five dominant learning models—problem-based learning, project-based learning, STEM education, inquiry learning, and discovery learning—as effective in fostering conceptual understanding, reflective thinking, and scientific reasoning. These models encourage students to explore, connect, and apply scientific concepts in authentic contexts. The findings highlight that innovative pedagogical approaches grounded in deep learning principles can transform science education by promoting higher-order thinking, sustainable learning, and the development of scientifically literate citizens